Weight Loss Following Orthognathic Surgery: a Descriptive Prospective Cohort Study - Tina Mosgaard Mogensen; Karin Bundgaard; Birgitte Boll; Niels Henrik Bruun; Thomas Starch-Jensen; Marie Germund Nielsen (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this prospective cohort study was to assess weight loss in kg following orthognathic surgery focusing on gender, type of surgery, employment, and living arrangements, as effect modifiers.